Materialitet Teoretiska tillämpningar i konstvetenskap 4 - Manker, Elin; Snickare, Mårten (Basic Readings in Culture and Aesthetics, 2023)
Among the literature aimed at students of art science and other image-interpreting sciences are a number of texts that deal with theories and theoretical concepts. However, what is largely missing, and which students often call for, are texts in Swedish that show how theories and concepts can be applied in concrete interpretation situations. The series Theoretical applications in art science aims to fill that gap, with the book Materiality being the fourth in the series. The book introduces and activates a concept that in recent decades has come to take an increasingly important place in humanistic research. Art scholars - but also archaeologists, anthropologists, literary scholars, ethnologists and other humanistic researchers - are increasingly interested in the material conditions for, and the manifestations of, people's social and cultural life and exchange. But despite its topicality in today's scientific conversation, the concept of materiality can seem elusive and elusive. It moves all the way from the most tangible analyzes of the material components of a cultural artefact, to the somewhat impenetrable theorizations of objectivity, agents and networks that are usually sorted under the label ""new materialism"". However, the book Materialitet gives concrete examples of how the concept of materiality can open up interpretations of important layers of meaning in works of art and other cultural artifacts. After the initial introduction where different perspectives and conceptualisations of materiality are discussed, six researchers each do their own analysis based on their subject area. The chapters are based on new research and are written specifically for this book. The different chapters together show the multifaceted nature of the concept of materiality, but do not lock it down to a definition, but open the eyes to a number of different interpretive paths.